Dual inflammation in schizophrenia infected with COVID-19: Impact on cognitive function - Qi Zhou; Jiayi Li; Jiahui Zhu; Mingqia Wang; Zhuokai Zhang; Jiamin Shao; Peng Wang; Xuan Dong; Gangming Cheng; Yuan Liu; Chuan Shi (Brain, Behavior, & Immunity - Health)
Background: Accumulating evidence has shown that cognitive function among schizophrenia is pervasively impaired and has a connection between immune-inflammatory markers. COVID-19 elicited a series of inflammatory cascades. However, in the context of dual inflammation, fluctuations in cognitive function of schizophrenia in the long-term remain unknown. We aimed to explore the effect of dual inflammation on cognitive domains of schizophrenia patients. Methods: This study included 119 schizophrenia patients with COVID-19 (49 recruited in the acute period and 70 recruited 2 years after recovery) and 114 schizophrenia patients without COVID-19, and 13 immune-inflammatory markers in the acute period were measured. Cognitive function of 119 patients with COVID-19 and 98 patients without COVID-19 were measured with Chinese Brief Cognitive Test (C-BCT) during the recruitment. General linear model was used to compare the immune-inflammatory markers, and correlation analysis was used to explore the relationship of inflammatory levels and cognitive function. Results: The peripheral immune-inflammatory levels of schizophrenia with COVID-19 were obviously increased (P values < 0.05). All domains of cognitive function of schizophrenia patients with COVID-19 were impaired notably in the acute period (all P values < 0.05), while were not worse than that of patients without COVID-19. However, there was no significant correlation between inflammatory markers and domains of cognitive function (P values > 0.05). Conclusion: This study found that schizophrenia patients with COVID-19 suggested dual inflammation, and cognitive function were impaired under dual inflammation. The cognitive impairment could be reversible in the long-term of recovery of inflammation.